Sustainable Competitive Decline Analysis of Small Medium Wood Crafts Industry in Bali - Gede Adi Yuniarta; I Gusti Ayu Purnamawati (Petra International Journal of Business Studies, 2023)
The development of production and export of wood crafts in Bali yearly tends to remain the same. This phenomenon shows a decline in the sustainable competitiveness of woodcraft SMEs in Bali. This study analyzes the variables that affect the competitiveness of woodcraft SMEs in Bali, including the role of the Government, HR competence, marketing performance, social environment, digitalization technology, and production performance. Data were collected by observation and interview methods and then analyzed with the subject of the study being MSME actors in Bali Province by determining the sample using probability sampling—data analysis using Partial Least Square Path Modeling (PLS-PM). The study results indicate that the role of government, implementation of corporate social responsibility, contextual factors, and business competence affect the competitiveness of the wood craft industry in Bali.